Eksplisitasi dalam Penerjemahan Novel Confessions: Analisis Appraisal Berbasis Kajian Korpus Linguistik - Lupita Parameswari; Doni Jaya (Peneliti.net, 2022)
The purpose of this paper is to analyze translation procedures applied and the changes of attitude subsystems in Indonesian edition of Confessions, published by Penerbit Haru and translated by Clara Canceriana and Andry Setiawan. The analysis is based on translation theory and types by Dewi and Wijaya (2021) and applying the appraisal theory by Martin and White (2005) as the focus of the research. The sample of the research is chapter one of Japanese and Indonesian edition of Confessions. This research used Sketch Engine, Antconc, and SegmentAnt as the chosen corpus tools to process the data. The findings show that there is a considerable number of attitude subsystem changes, in which the number of subsystems in Indonesian edition is higher than that in Japanese edition.